Bilateral metastatic breast cancer as the first manifestation of ovarian cancer: Case report - (:unkn) unknown (I R O G CANADA, INC, 2005)
Background: Breast metastasis from primary ovarian cancer is extremely rare. The rarity of this finding may be the reason for its common misinterpretation as primary breast carcinoma. Design: Case report. Setting: A university hospital. Results: A case of a patient with primary ovarian papillary serous cystadenocarcinoma who initially presented with a solitary bilateral breast mass and abdominal distention is reported. Conclusions: Blood-borne metastasis from the ovary to the breast can show a varied clinical picture that should be differentiated from that of primary breast carcinoma.
Keywords: bilateral; breast cancer; metastatic; ovarian cancer; CARCINOMA METASTASIS